# Library prosa.util.sum

From mathcomp Require Import ssreflect ssrbool eqtype ssrnat seq fintype bigop path.

Require Export prosa.util.notation.
Require Export prosa.util.rel.
Require Export prosa.util.nat.

Section SumsOverSequences.

Consider any type I with a decidable equality ...
Variable (I : eqType).

... and assume we are given a sequence ...
Variable (r : seq I).

... and a predicate P.
Variable (P : pred I).

First, we will show some properties of the sum performed over a single function yielding natural numbers.
Section SumOfOneFunction.

Consider any function that yields natural numbers.
Variable (F : I nat).

We start showing that having every member of r equal to zero is equivalent to having the sum of all the elements of r equal to zero, and vice-versa.
Lemma sum_nat_eq0_nat :
(\sum_(i <- r | P i) F i == 0) = all (fun xF x == 0) [seq x <- r | P x].
Proof.
elim: r ⇒ [|x r' IH]; rewrite ?big_nil//= big_cons.
by case: ifP; rewrite ?addn_eq0 IH.
Qed.

In the same way, if at least one element of r is not zero, then the sum of all elements of r must be strictly positive, and vice-versa.
Lemma sum_nat_gt0 :
(0 < \sum_(i <- r | P i) F i) = has (fun x ⇒ 0 < F x) [seq x <- r | P x].
Proof.
apply/negb_inj; rewrite lt0n negbK sum_nat_eq0_nat -all_predC.
by apply/eq_all ⇒ ?; rewrite /= lt0n negbK.
Qed.

Next, we show that if a number a is not contained in r, then filtering or not filtering a when summing leads to the same result.
Lemma sum_notin_rem_eqn a :
a \notin r
\sum_(x <- r | P x && (x != a)) F x = \sum_(x <- r | P x) F x.
Proof.
movea_notin_r; rewrite [LHS]big_seq_cond [RHS]big_seq_cond.
apply: eq_biglx; case xinr: (x \in r) ⇒ //=.
have [xa|] := eqP; last by rewrite andbT.
by move: xinr a_notin_r; rewrite xa ⇒ →.
Qed.

We prove that if any element of r is bounded by constant c, then the sum of the whole set is bounded by c × size r.
Lemma sum_majorant_constant c :
( a, a \in r P a F a c)
\sum_(j <- r | P j) F j c × (size [seq j <- r | P j]).
Proof.
moveFa_le_c.
rewrite -sum1_size big_filter big_distrr/= muln1.
rewrite big_seq_cond [X in _ X]big_seq_cond.
apply: leq_sumi /andP[ir Pi]; exact: Fa_le_c.
Qed.

Next, we show that the sum of the elements in r respecting P can be obtained by removing from the total sum over r the sum of the elements in r not respecting P.
Lemma sum_pred_diff:
\sum_(r <- r | P r) F r = \sum_(r <- r) F r - \sum_(r <- r | ~~ P r) F r.
Proof. by rewrite [X in X - _](bigID P)/= addnK. Qed.

End SumOfOneFunction.

In this section, we show some properties of the sum performed over two different functions.
Section SumOfTwoFunctions.

Consider three functions that yield natural numbers.
Variable (E E1 E2 : I nat).

Besides earlier introduced predicate P, we add two additional predicates P1 and P2.
Variable (P1 P2 : pred I).

Assume that E2 dominates E1 in all the points contained in the set r and respecting the predicate P. We prove that, if we sum both function over those points, then the sum of E2 will dominate the sum of E1.
Lemma leq_sum_seq :
( i, i \in r P i E1 i E2 i)
\sum_(i <- r | P i) E1 i \sum_(i <- r | P i) E2 i.
Proof.
movele; rewrite big_seq_cond [X in _ X]big_seq_cond.
apply: leq_sumi /andP[]; exact: le.
Qed.

In the same way, if E1 equals E2 in all the points considered above, then also the two sums will be identical.
Lemma eq_sum_seq:
( i, i \in r P i E1 i == E2 i)
\sum_(i <- r | P i) E1 i == \sum_(i <- r | P i) E2 i.
Proof.
moveeqE; apply/eqP; rewrite -big_filter -[RHS]big_filter.
apply: eq_big_seqx; rewrite mem_filter ⇒ /andP[Px xr]; exact/eqP/eqE.
Qed.

Assume that P1 implies P2 in all the points contained in the set r. We prove that, if we sum both functions over those points, then the sum of E conditioned by P2 will dominate the sum of E conditioned by P1.
Lemma leq_sum_seq_pred:
( i, i \in r P1 i P2 i)
\sum_(i <- r | P1 i) E i \sum_(i <- r | P2 i) E i.
Proof.
moveimp; rewrite [X in _ X](bigID P1)/=.
rewrite big_seq_cond [X in _ X + _]big_seq_cond.
rewrite (eq_bigl (fun i[&& i \in r, P2 i & P1 i])) ?leq_addr// ⇒ i.
by case ir: (i \in r); case P1i: (P1 i); rewrite ?andbF //= (imp i).
Qed.

End SumOfTwoFunctions.

End SumsOverSequences.

For technical (and temporary) reasons related to the proof style, the next two lemmas are stated outside of the section, but conceptually make use of a similar context.
First, we observe that summing over a subset of a given sequence, if all summands are natural numbers, cannot yield a larger sum.
Lemma leq_sum_subseq (I : eqType) (r r' : seq I) (P : pred I) (F : I nat) :
subseq r r'
\sum_(i <- r | P i) F i \sum_(i <- r' | P i) F i.
Proof.
elim: r r' ⇒ [|x r IH] r'; first by rewrite big_nil.
elim: r' ⇒ [//|x' r' IH'] /=; have [<- /IH {}IH|_ /IH' {}IH'] := eqP.
- by rewrite !big_cons; case: (P x); rewrite // leq_add2l.
- rewrite [X in _ X]big_cons; case: (P x') ⇒ //.
Qed.

Second, we repeat the above observation that summing a superset of natural numbers cannot yield a lesser sum, but phrase the claim differently.
Requiring the absence of duplicate in r is a simple way to guarantee that the set inclusion r rs implies the actually required multiset inclusion.
Lemma leq_sum_sub_uniq (I : eqType) (r : seq I) (F : I nat) (rs : seq I) :
uniq r {subset r rs}
\sum_(i <- r) F i \sum_(i <- rs) F i.
Proof.
moveuniq_r sub_r_rs.
rewrite [X in _ X](bigID (fun xx \in r))/=.
rewrite (perm_big (undup [seq x <- rs | x \in r])).
- rewrite -filter_undup big_filter_cond/=.
under eq_bigl ⇒ ? do rewrite andbT; exact/leq_sum_subseq/undup_subseq.
- apply: uniq_perm; rewrite ?undup_uniq// ⇒ x.
rewrite mem_undup mem_filter.
by case xinr: (x \in r); rewrite // (sub_r_rs _ xinr).
Qed.

We continue establishing properties of sums over sequences, but start a new section here because some of the below proofs depend lemmas in the preceding section in their full generality.
Consider any type I with a decidable equality ...
Variable (I : eqType).

... and assume we are given a sequence ...
Variable (r : seq I).

... and a predicate P.
Variable (P : pred I).

Consider two functions that yield natural numbers.
Variable (E1 E2 : I nat).

First, as an auxiliary lemma, we observe that, if E1 j is less than E2 j for some element j involved in a summation (filtered by P), then the corresponding totals are not equal.
Lemma ltn_sum_leq_seq j :
j \in r
P j
E1 j < E2 j
( i, i \in r P i E1 i E2 i)
\sum_(x <- r | P x) E1 x < \sum_(x <- r | P x) E2 x.
Proof.
movejr Pj ltj le.
rewrite (big_rem j)// [X in _ < X](big_rem j)//= Pj -addSn leq_add//.
apply: leq_sum_seqi /mem_rem; exact: le.
Qed.

Next, we prove that if for any element i of a set r the following two statements hold (1) E1 i is less than or equal to E2 i and (2) the sum E1 x_1, ..., E1 x_n is equal to the sum of E2 x_1, ..., E2 x_n, then E1 x is equal to E2 x for any element x of xs.
Lemma eq_sum_leq_seq :
( i, i \in r P i E1 i E2 i)
\sum_(x <- r | P x) E1 x == \sum_(x <- r | P x) E2 x
= all (fun xE1 x == E2 x) [seq x <- r | P x].
Proof.
movele; rewrite all_filter; case aE: all.
apply: eq_sum_seqi ir Pi; move: aE ⇒ /allP/(_ i ir)/implyP; exact.
have [j /andP[jr Pj] ltj] : exists2 j, (j \in r) && P j & E1 j < E2 j.
have /negbT := aE; rewrite -has_predC ⇒ /hasP[j jr /=].
rewrite negb_imply ⇒ /andP[Pj neq].
- by j; first exact/andP; rewrite ltn_neqAle neq le.
- by apply/negbTE; rewrite neq_ltn (ltn_sum_leq_seq j).
Qed.

End SumsOverSequences.

In this section, we prove a variety of properties of sums performed over ranges.
Section SumsOverRanges.

First, we prove that the sum of Δ ones is equal to Δ .
Lemma sum_of_ones:
t Δ,
\sum_(t x < t + Δ) 1 = Δ.

Next, we show that a sum of natural numbers equals zero if and only if all terms are zero.
Lemma big_nat_eq0 m n F:
\sum_(m i < n) F i = 0 ( i, m i < n F i = 0).
Proof.
split.
- rewrite /index_iota ⇒ /eqP.
rewrite sum_nat_eq0_nat filter_predT ⇒ /allP ZERO i.
rewrite -mem_index_iota /index_iotaIN.
by apply/eqP; apply ZERO.
- moveZERO.
have→ : \sum_(m i < n) F i = \sum_(m i < n) 0 by apply eq_big_nat.
exact: big1_eq.
Qed.

Moreover, the fact that the sum is smaller than the range of the summation implies the existence of a zero element.
Lemma sum_le_summation_range:
f t Δ,
\sum_(t x < t + Δ) f x < Δ
x, t x < t + Δ f x = 0.
Proof.
induction Δ; intros; first by rewrite ltn0 in H.
destruct (f (t + Δ)) eqn: EQ.
{ (t + Δ); split; last by done.
feed IHΔ.
{ by apply leq_ltn_trans with (\sum_(t i < t + Δ) f i + n); first rewrite leq_addr. }
move: IHΔ ⇒ [z [/andP [LE GE] ZERO]].
z; split; last by done.
apply/andP; split; first by done.
by rewrite ltnS ltnW. }
Qed.

Next, we prove that the summing over the difference of two functions is the same as summing over the two functions separately, and then taking the difference of the two sums. Since we are using natural numbers, we have to require that one function dominates the other in the summing range.
Lemma sumnB_nat m n F G :
( i, m i < n F i G i)
\sum_(m i < n) (F i - G i) =
(\sum_(m i < n) (F i)) - (\sum_(m i < n) (G i)).
Proof.
movele.
rewrite big_nat_cond [X in X - _]big_nat_cond [X in _ - X]big_nat_cond.
rewrite sumnB// ⇒ i; rewrite andbT; exact: le.
Qed.

End SumsOverRanges.

In this section, we show how it is possible to equate the result of two sums performed on two different functions and on different intervals, provided that the two functions match point-wise.
Consider two equally-sized intervals `[t1, t1+d)` and `[t2, t2+d)`...
Variable (t1 t2 : nat).
Variable (d : nat).

...and two functions F1 and F2.
Variable (F1 F2 : nat nat).

Assume that the two functions match point-wise with each other, with the points taken in their respective interval.
Hypothesis equal_before_d: g, g < d F1 (t1 + g) = F2 (t2 + g).

The then summations of F1 over `[t1, t1 + d)` and F2 over `[t2, t2 + d)` are equal.
Lemma big_sum_eq_in_eq_sized_intervals:
\sum_(t1 t < t1 + d) F1 t = \sum_(t2 t < t2 + d) F2 t.
Proof.
induction d; first by rewrite !addn0 !big_geq.
rewrite !addnS !big_nat_recr ⇒ //; try by lia.
rewrite IHn //=; last by moveg G_LTl; apply (equal_before_d g); lia.
by rewrite equal_before_d.
Qed.

End SumOfTwoIntervals.

In this section, we relate the sum of items with the sum over partitions of those items.
Consider an item type X and a partition type Y.
Variable X Y : eqType.

x_to_y is the mapping from an item to the partition it is contained in.
Variable x_to_y : X Y.

Consider f, a function from X to nat.
Variable f : X nat.

Consider an arbitrary predicate P on X.
Variable P : pred X.

Consider a sequence of items xs and a sequence of partitions ys.
Variable xs : seq X.
Variable ys : seq Y.

We assume that any item in xs has its corresponding partition in the sequence of partitions ys.
Hypothesis H_no_partition_missing : x, x \in xs x_to_y x \in ys.

Consider the sum of f x over all x in a given partition y.
We prove that summation of f x over all x is less than or equal to the summation of sum_of_partition over all partitions.
Lemma sum_over_partitions_le :
\sum_(x <- xs | P x) f x
\sum_(y <- ys) sum_of_partition y.
Proof.
rewrite /sum_of_partition.
induction xs as [| x' xs' LE_TAIL]; first by rewrite big_nil.
have P_HOLDS: i j, true P j && (x_to_y j== i) P j by move⇒ ??? /andP [P_HOLDS _].
have IN_ys: x : X, x \in xs' x_to_y x \in ys.
{ by move⇒ ??; apply H_no_partition_missing ⇒ //; rewrite in_cons; apply /orP; right. }
move: LE_TAIL; rewrite (exchange_big_dep P) ⇒ //= LE_TAIL.
rewrite (exchange_big_dep P) //= !big_cons.
case: (P x') ⇒ //=; last by apply LE_TAIL.
apply leq_add ⇒ //; last by apply LE_TAIL.
apply leq_pmulr; rewrite -has_count.
apply /hasP; eapply ex_intro2 ⇒ //.
Qed.

Consider a partition y'.
Variable y' : Y.

We prove that the sum of items excluding all items from a partition y' is less-than-or-equal to the sum over all partitions except y'.
Lemma reorder_summation : \sum_(x <- xs | P x && (x_to_y x != y')) f x
\sum_(y <- ys | y != y') sum_of_partition y.
Proof.
rewrite (exchange_big_dep (fun xP x && (x_to_y x != y'))) //=.
- rewrite big_seq_cond [X in _ X]big_seq_cond.
apply leq_sumx' /andP [ARRo /andP [Px' NEQ]].
rewrite (big_rem (x_to_y x')) //=.
rewrite Px' eq_refl NEQ andTb andTb leq_addr //.
by apply H_no_partition_missing.
- movey_of_x' x' /negP NEQ /andP [EQ1 /eqP EQ2].
rewrite EQ1 Bool.andb_true_l; apply/negP; intros CONTR.
apply: NEQ; clear EQ1.
by rewrite -EQ2.
Qed.

In this section, we prove a stronger result about the equality between the sum over all items and the sum over all partitions of those items.
Section Equality.

In order to prove the stronger result of equality, we additionally assume that the sequences xs and ys are sets, i.e., that each element is contained at most once.
Hypothesis H_xs_unique : uniq xs.
Hypothesis H_ys_unique : uniq ys.

We prove that summation of f x over all x is equal to the summation of sum_of_partition over all partitions.
Lemma sum_over_partitions_eq :
\sum_(x <- xs | P x) f x
= \sum_(y <- ys) sum_of_partition y.
Proof.
rewrite /sum_of_partition.
induction xs as [|x' xs' LE_TAIL]; first by rewrite big_nil big1_seq //= ⇒ ??; rewrite big_nil.
rewrite //= in LE_TAIL; feed_n 2 LE_TAIL.
{ by move ⇒ ??; apply H_no_partition_missing; rewrite in_cons; apply /orP; right. }
{ by move: H_xs_unique; rewrite cons_uniq ⇒ /andP [??]. }
rewrite (exchange_big_dep P) //=; last by move⇒ ??? /andP[??].
rewrite !big_cons.
destruct (P x'); last by rewrite LE_TAIL (exchange_big_dep P) //=; move⇒ ??? /andP[??].
have → : \sum_(i <- ys | true && ( x_to_y x' == i)) f x' = f x'.
{ rewrite //= -big_filter.
have → : [seq i <- ys | x_to_y x' == i] = [:: x_to_y x']; last by rewrite unlock //= addn0.
have → : [seq i <- ys | x_to_y x' == i] = [seq i <- ys | i == x_to_y x'].
{ clear H_no_partition_missing LE_TAIL.
induction ys as [| y'' ys' LE_TAILy]; first by done.
feed LE_TAILy; first by move: H_ys_unique; rewrite cons_uniq ⇒ /andP [??].
by rewrite //= LE_TAILy //= eq_sym. }
apply filter_pred1_uniq ⇒ //.
by apply H_no_partition_missing; rewrite in_cons; apply /orP; left. }
apply /eqP; rewrite eqn_add2l; apply /eqP.
by rewrite LE_TAIL (exchange_big_dep P) //=; move⇒ ??? /andP[??].
Qed.

End Equality.

End SumOverPartitions.

We observe a trivial monotonicity-preserving property with regard to leq.
Section Monotonicity.

Consider any type of indices, any predicate, ...
Variables (I : eqType) (P : pred I).

... and any function that maps each index to a nat nat function.
Variable F : I nat nat.

Consider any set of indices ...
Variable r : seq I.

... and suppose that F i is monotonic with regard to leq for every index in r.
Hypothesis H_mono : i, i \in r monotone leq (F i).

Consider the sum of F over r, for any given x.
Let f x := \sum_(i <- r | P i) F i x.

We note that this sum f is monotonic with regard to leq in x.
Lemma sum_leq_mono :
monotone leq f.
Proof.
movex y LEQ.
rewrite /f big_seq_cond [in X in _ X]big_seq_cond.
apply: leq_sumi /andP [IN _].
by apply: H_mono.
Qed.

End Monotonicity.